Business ethics and social responsibility - Fernandez,Maria Rosario C. (Makati City : Diwa Learning Systems, Inc., 2020)
"In the recent times, the challenge of addressing ethical issues has confronted various companies---large and small alike--not only in the country but also worldwide.Business Ethics and Social Responsibility (Second Edition) will help the students to be in tune with the emerging needs and trends in business operation.This book will be yur guide in learning and teaching ethical business practices and socially responsive programs that will impact the future of generation to come."
Includes bibliography.
English text.
Keywords: Business ethics; Social responsibility of business